2021
DOI: 10.3389/fpsyt.2021.769743
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and Insomnia Increase Suicidal Ideation in Schizophrenia Patients: A Cross-Sectional Study

Abstract: Objectives: This study aimed to investigate the effect of childhood trauma, especially its specific dimensions, and clinical risk factors for suicidal ideation in patients with schizophrenia.Methods: A total of 83 inpatients with schizophrenia were enrolled and divided into two groups: with suicidal ideation (n = 33) and without suicidal ideation (n = 50). All participants were administered the Childhood Trauma Questionnaire-Short Form, the Insomnia Severity Index, the Beck Scale for Suicide Ideation, the Modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…After searches and review of study methods, 10 studies met the criteria for inclusion [5,6 ▪ ,7,15 ▪ ,18,19,20 ▪ ,21–23]. Nine studies contributed data on insomnia and suicide, and eight studies contributed data on insomnia and psychopathology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After searches and review of study methods, 10 studies met the criteria for inclusion [5,6 ▪ ,7,15 ▪ ,18,19,20 ▪ ,21–23]. Nine studies contributed data on insomnia and suicide, and eight studies contributed data on insomnia and psychopathology.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is particularly relevant for patients with schizophrenia, given a 27% lifetime prevalence of suicide attempt [13] and a 5% lifetime prevalence of suicide death [14] in the disorder. Several studies have found that insomnia is an indicator of suicidal ideation, suicide attempt, and suicide death in patients with schizophrenia [5,6 ▪ ,7,15 ▪ ,16–19,20 ▪ ]. However, to our knowledge, these associations have not been systematically reviewed.…”
Section: Introductionmentioning
confidence: 97%
“…Life adversities during critical developmental stages of life, especially childhood, are associated with more severe and persistent symptoms that negatively affect health outcomes [47]. In addition, it is reported that physical abuse could increase the risk of suicide tendency in adolescents [48], young people [49], persons with MDD [50],…”
Section: Discussionmentioning
confidence: 99%
“…First, previous studies have produced highly varied results. 6 13 Several studies reported no association between childhood maltreatment and suicide ideation in people with chronic schizophrenia 10 or people with first-episode schizophrenia, 6 while other studies demonstrated a positive relationship. 7 , 11 …”
Section: Association Between Childhood Maltreatment and Suicidality I...mentioning
confidence: 99%
“… 16 , 17 However, the connection between suicidality and specific types of childhood maltreatment in individuals with schizophrenia remains debatable. For example, while physical neglect is highlighted as the sole predictor for suicide ideation in some studies, 11 , 13 one separate study in 216 Chinese people with schizophrenia demonstrated that suicide ideation was only positively correlated with emotional abuse and emotional neglect, but not with physical neglect. 12 Another study in individuals with relapse schizophrenia demonstrated that suicide ideation could be related to emotional neglect and sexual abuse, while suicide ideation was not associated with other types of childhood maltreatment.…”
Section: Association Between Childhood Maltreatment and Suicidality I...mentioning
confidence: 99%